Hochschild cohomology and orbifold Jacobian algebras associated to invertible polynomials - Basalaev, Alexey; Takahashi, Atsushi (Journal of noncommutative geometry, 2020)
Let f be an invertible polynomial and G a group of diagonal symmetries - of f . This note shows that the orbifold Jacobian algebra Jac(f, G) of (f, G) defined - by [BTW16] is isomorphic as a Z/2Z-graded algebra to the Hochschild cohomology - HH ∗ (MF G (f )) of the dg-category MF G (f ) of G-equivariant matrix factorizations of f - by calculating the product formula of HH ∗ (MF G (f )) given by Shklyarov [S17]. We also - discuss the relation of our previous results to the categorical equivalence.
Gesehen am 14.06.2021